Maxim Violation in Death Race Inferno 3 Movie - Putra, I Kadek Dwi Dharma; Suastini, Ni Wayan; Ariyaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2023)
According to Zor (2006), maxim violation that people tend to violate the maxims during the exchange of conversation quietly and unostentatiously when they fail to observe the maxim intentionally (as cited in Al-Qaderi , 2015,pp,80-81). Grice (1989 :28) said that when the speaker does not fulfill or obey the maxims, the speaker is said the violate the maxims. This study concerns with the type of maxim violation that appeared in movie of Death Race Inferno 3. The study aims to analyze the types of maxim violation that found in the movie. The data were taken from the movie of Death Race Inferno 3 that has been downloaded from FlashNet.com and they are collected through observation and note taking technique. The theory of Grice (1975) is used to analyse the maxim violation type. The result shows that there are some maxim violations appear in the movie and are uttered by the characters in the movie. The study concludes that in the movie there are found 15 of maxim violations, 3 violation maxim of quantity, 3 violation maxim of quality, 6 violation maxim of relevance and 3 violations maxim of manner.